Career Development and Hermeneutical Inquiry Part II. Undertaking Hermeneutical research - Collin, Audrey; Young, Richard A. (Canadian Journal of Counselling and Psychotherapy, 2011)
Three hermeneutical or quasi-hermeneutical studies in the career development domain are used to illustrate important dimensions of this type of research. Among the methodology and techniques illustrated are collecting, recording, and analyzing the research material and presenting the interpretative framework. The following significant issues to hermeneutical researchers are addressed: subjectivity, reliability, validity, accessibility, feasibility, and confidentiality.